Chemokine Regulation During Epidemic Coronavirus Infection - Majumdar, Shamik; Murphy, Philip M. (Frontiers in Pharmacology, 2021)
SARS-CoV-2 (Severe Acute Respiratory Syndrome coronavirus-2) is the third coronavirus to emerge as a cause of severe and frequently fatal pneumonia epidemics in humans, joining SARS-CoV and MERS-CoV (Middle East Respiratory Syndrome-coronavirus). As with many infectious diseases, the immune response to coronavirus infection may act as a double-edged sword: necessary for promoting antiviral host defense, but, if not appropriately regulated, also able to incite life-threatening immunopathology. Key immunoregulatory mediators include the chemokines, a large family of leukocyte chemoattractants that coordinate leukocyte infiltration, positioning and activation in infected tissue by acting at specific G protein-coupled receptors. Here, we compare the involvement of chemokines and chemokine receptors during infection with the three epidemic coronaviruses and discuss their potential value as biomarkers and targets for therapeutic development.